Homophobia in primary schools: does it exist? - Alan Hodkinson; Colin Wong (Educational Futures)
This paper outlines research into homophobia in primary schools that was conducted with academics, support staff and students engaged in initial teacher training at a university in the North West of England and teaching staff from local primary schools. The research involved the use of questionnaires, semi-structured and unstructured interview to gain insight into the existence of homophobia in primary schools. The data from the study suggests that homophobia exists within primary settings and that children as young as five employ discriminatory language. The study details that incidents of homophobia include those related to gender identity; perceptions of masculinity and femininity; school and workplace bullying and multimedia coverage of homosexuality. The study demonstrates that barriers to tackling homophobia exist in primary schools and that these may stem from staff, parental attitudes, school policy and issues relating to faith and religion.